Bacillus lipopeptide-mediated biocontrol of peanut stem rot caused by Athelia rolfsii - Korangi Alleluya, Virginie; Argüelles Arias, Anthony; Ribeiro, Bianca; De Coninck, Barbara; Helmus, Catherine; Delaplace, Pierre; Ongena, Marc (Frontiers in Plant Science, 2023)
Peanut (Arachis hypogaea L.) is a widespread oilseed crop of high agricultural importance in tropical and subtropical areas. It plays a major role in the food supply in the Democratic Republic of Congo (DRC). However, one major constraint in the production of this plant is the stem rot (white mold or southern blight) disease caused by Athelia rolfsii which is so far controlled mainly using chemicals. However, the implementation of eco-friendly alternatives such as biological control is required for disease management in a more sustainable agriculture in the DRC as in the other developing countries concerned. Bacillus velezensis is among the rhizobacteria best described for its plant protective effect notably due to the production of a wide range of bioactive secondary metabolites. In this work, we wanted to evaluate the potential of B. velezensis strain GA1 at reducing A. rolfsii infection and to unravel the molecular basis of the protective effect. Upon growth under the nutritional conditions dictated by peanut root exudation, the bacterium efficiently produces the three types of lipopeptides surfactin, iturin and fengycin known for their antagonistic activities against a wide range of fungal phytopathogens. By testing a range of GA1 mutants specifically repressed in the production of those metabolites, we point out an important role for iturin and another unidentified compound in the antagonistic activity against the pathogen. Biocontrol experiments performed in greenhouse further revealed the efficacy of B. velezensis to reduce peanut disease caused by A. rolfsii both via direct antagonism against the fungus and by stimulating systemic resistance in the host plant. As treatment with pure surfactin yielded a similar level of protection, we postulate that this lipopeptide acts as main elicitor of peanut resistance against A. rolfsii infection.